‘Ossi di Seppia’? The Tithes Between Lords and Rural Communities (Lombardy, 13th-15th Centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
In Late-Medieval Lombardy, social, economic and institutional changes weakened seigniorial control over tithes; rural lords were often replaced by new players (i.e. rural communities, urban aristocracy). In this essay, I will first analyze this transition; then, I will examine the seigniorial management of tithes. The strategies adopted by the lords to control this right, the negotiations with the rural communities, and the ways of managing this important economic income allow us to understand relevant aspects of the seigniorial power in Lombardy at the end of the Middle Ages.
Keywords: Tithes management; rural lordship; rural communities; Lombardy